Shared Governance and Systems Theory: A Mixed Methods Study of Faculty Perceptions and Ideas (Higher Education Politics and Economics, 2023)
At a time when higher education faces serious existential challenges, it is important for stakeholders in higher education to come together to make important decisions that are thoughtful and internally legitimate. Shared governance, a concept that is widely touted yet wildly varied in implementation, is the best path forward for decision makers. In an effort to better understand shared governance and how it might best be practiced, this mixed-methods study uses data from faculty at one university to develop a model and a specific set of recommendations for shared governance reform. Viewed through the lens of systems theory, data analysis leads to a model that considers cultural and structural changes for shared governance that are cyclical and systemic.